Topics in Modern Physics : Solutions to Problems - Amore, Paolo; Walecka, John dirk (Singapore: World Scientific, 2015)
Our understanding of the physical world was revolutionized in the twentieth century -- the era of "modern physics". Two books by the second author entitled Introduction to Modern Physics: Theoretical Foundations and Advanced Modern Physics: Theoretical Foundations, aimed at the very best students, present the foundations and frontiers of today's physics. Many problems are included in these texts. A previous book by the current authors provides solutions to the over 175 problems in the first volume.A third volume Topics in Modern Physics: Theoretical Foundations has recently appeared, which covers several subjects omitted in the essentially linear progression in the previous two. This book has three parts: part 1 is on quantum mechanics, part 2 is on applications of quantum mechanics, and part 3 covers some selected topics in relativistic quantum field theory. Parts 1 and 2 follow naturally from the initial volume. The present book provides solutions to the over 135 problems in this third volume.The three volumes in this series, together with the solutions manuals, provide a clear, logical, self-contained, and comprehensive base from which students can learn modern physics. When finished, readers should have an elementary working knowledge in the principal areas of theoretical physics of the twentieth century.
Appendix A-B 255-260p.; Bibliography 261-264p.; Index 265-271p.
Keywords: Discrete symmetries; Heisenberg picture; Scattering theory; Formal developments